2005
DOI: 10.2136/sssaj2004.0166
|View full text |Cite
|
Sign up to set email alerts
|

Binding of DNA from Bacillus subtilis on Montmorillonite–Humic Acids–Aluminum or Iron Hydroxypolymers

Abstract: The equilibrium adsorption and binding of DNA from Bacillus subtilis on complexes of montmorillonite–humic acids Al or Fe hydroxypolymers (Al–M–HA or Fe–M–HA) at different M/HA ratios, the desorption of DNA, the capacity of bound DNA to transform competent cells of B. subtilis in vitro, and the protection of bound DNA from degradation by free and organomineral‐bound DNase I are reported. Adsorption was rapid (maximal after 2 h), occurred from pH 3 to 10, and was higher on Al–M–HA than on Fe–M–HA. Saturation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…Incubations of ferruginous sediments from Lake Matano showed that hydrous ferric oxides (i.e., ferrihydrite) are rapidly reduced by dissimilatory metal-reducing bacteria, resulting in the dissolution of Fe–Mn oxyhydroxides with persistence of mainly goethite (Crowe et al, 2007a,b). The affinity of DNA for goethite is substantially lower than that of common phyllosilicates (Cai et al, 2006), and because goethite traps organic molecules indifferently, its sorption capacity also decreases with increasing organic matter content and degradation (Crecchio et al, 2005). Complete reduction of ferrihydrite occurs within the first cm of sediment at the shallow site, whereas it is even absent at the deep site due to its prior reduction in the water column (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incubations of ferruginous sediments from Lake Matano showed that hydrous ferric oxides (i.e., ferrihydrite) are rapidly reduced by dissimilatory metal-reducing bacteria, resulting in the dissolution of Fe–Mn oxyhydroxides with persistence of mainly goethite (Crowe et al, 2007a,b). The affinity of DNA for goethite is substantially lower than that of common phyllosilicates (Cai et al, 2006), and because goethite traps organic molecules indifferently, its sorption capacity also decreases with increasing organic matter content and degradation (Crecchio et al, 2005). Complete reduction of ferrihydrite occurs within the first cm of sediment at the shallow site, whereas it is even absent at the deep site due to its prior reduction in the water column (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It includes nucleic acids from damaged dead cells, released upon lysis or actively excreted into the surrounding water and sediment (Torti et al, 2015). This fraction is partitioned between sorption onto mineral matrices (Crecchio et al, 2005; Cleaves et al, 2011) and degradation via microbial metabolism (Corinaldesi et al, 2007). Adsorption promotes its persistence, and deposition and burial in sediments, whereas free DNA is readily available for microbial uptake as a nutrient source, resulting in variable turnover rates of this fraction (Dell’Anno and Corinaldesi, 2004; Corinaldesi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Although most plant-derived DNA in soil can be rapidly degraded by biotic and abiotic factors, [10] long-term persistence of plant DNA in soil was frequently reported, especially when DNA was adsorbed to soil particles. [6,[11][12][13][14] Further, DNA adsorbed to mineral surfaces can be protected from degradation, and thus maintains its integrity. [6,13] Recent studies showed that plant DNA including transgene DNA can be detected in soil samples collected from field trials all year-round when GM plants were grown under continuous cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigations have been devoted to the adsorption and binding of DNA on various soil components such as sand, clay minerals, humic substances and soils. It was found that this process is affected by the ionic strength, pH of the medium, type and content of clay as well as the characteristics and configurations of DNA molecules [12][13][14][15][16][17]. An increase in the concentration of cations and/or a decrease in the pH favored DNA adsorption on soil colloids and clay minerals [12][13][14].…”
Section: Introductionmentioning
confidence: 99%